Sistem Kebijakan Rekrutmen Penyelenggara Anggota KPPS Yang Berintegritas Untuk Pemilu 2024 - Taffy Faiq Syahmi; Mega Dewi Ambarwati (CV Edujavare Publishing, 2024)
This simultaneous election marks a new chapter in the history of Indonesian democracy. The core of the election process is the group of polling organizers known as the KPPS. One of the problems in the growth of Indonesian democracy is the implementation of fair and honest elections. Election organizers are one of the key players in the election process. In order for elections to be of high quality, organizers must be responsible, impartial, and professional. The election results have always been marred by allegations of fraud and organizers accused of not being independent in the latest legislative and executive elections (presidential and regional head elections). The problem is that the requirements set by the KPPS do not match. Recruitment of KPPS Election members requires a decision support system, especially a decision support system for KPPS Election recruitment, in order to solve this problem. The system development model used in building the system is the waterfall model. By building a decision support system for KPPS Election member recruitment, it can help PPS in making decisions to determine qualified KPPS members.